Implementation of Authentic Assessment among Social Studies Teachers in The Private Catholic Schools during Covid-19 Pandemic - Gorromeo, Ednalyn M. (Future Science / FSH-PH Publications, 2025)
This research investigated the struggles faced by educators in implementing Authentic Assessment at Private Catholic Educa-tional Institutes within the Diocese of Iba during the 2022-2023 school year, specifically in the 3rd Quarter period. A descriptive research method using a survey questionnaire was employed to gather data from 101 Social Studies teachers. The findings indi-cated that the majority of respondents were female, single, col-lege-educated, and had been teaching for over five years. The respondents expressed confidence in their knowledge of imple-menting Authentic Assessment during the COVID-19 pandemic. Visual and kinesthetic methods were frequently used, with re-sponses indicating these were employed